Effects of 4 Weeks of Explosive-type Strength Training for the Plantar Flexors on the Rate of Torque Development and Postural Stability in Elderly Individuals - Kobayashi, Y.; Ueyasu, Y.; Yamashita, Y.; Akagi, R. (International Journal of Sports Medicine, 2016)
This study aimed to investigate the effect of a 4-week explosive-type strength training program for the plantar flexors on the rate of torque development and postural stability. The participants were 56 elderly men and women divided into training (17 men and 15 women) and control (14 men and 10 women) groups. The participants in the training group underwent explosive-type strength training of the plantar flexors 2 days per week for 4 weeks. Training consisted of 3 sets of 10 repetitions of explosive plantar flexion lasting less than 1 s. The following parameters were determined: muscle volume of the plantar flexors estimated by the muscle thickness and lower leg length, maximal voluntary contraction torque and rate of torque development of plantar flexion, and one-leg standing ability. The training increased the maximal voluntary contraction torque and rate of torque development, but corresponding increases in muscle volume and one-leg standing ability were not found. These results suggest that, for elderly individuals, the 4-week explosive-type strength training of the plantar flexors is effective for increasing the maximal voluntary contraction torque and rate of torque development of plantar flexion but is not effective for improving postural stability.
Keywords: one-leg standing ability; maximal voluntary contraction; muscle volume; plantar flexion; electromyography